The Implementation of the Qur'an Memorization Program through the Tahfizul Qur'an Quarantine Program at Darul Hijrah Putra Islamic Boarding School, Cindai Alus - Laila Mawaddah; Mardhiya Agustina; Khalilurrahman Khalilurrahman (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study was motivated by the rapid growth of Qur'an memorization (Tahfidz) programs in Indonesia, encouraging Islamic educational institutions to implement intensive memorization programs. Darul Hijrah Islamic Boarding School, Putra Cindai Alus, is one of the institutions that organizes the Qur'an Memorization Quarantine Program. However, several challenges remain, preventing the program from being implemented optimally. This study aimed to describe the implementation of the Qur'an Memorization Quarantine Program, focusing on its planning, implementation, and evaluation stages. A qualitative field research approach was employed. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the planning stage involved establishing learning objectives, organizing learning materials according to participants' initial abilities, applying the Yadain Litahfizhil Qur'an method integrated with talaqqi and muraja'ah, designing learning strategies, preparing instructional media, and developing evaluation procedures. The implementation stage consisted of opening activities, memorization sessions, recitation submission, muraja'ah, recitation correction, mentoring, and closing activities involving prayers and motivation. Meanwhile, the evaluation stage included continuous supervision by muhafiz, muhafizah, and the organizing committee, as well as assessments of memorization achievement, tajwid, discipline, and students' manners through daily, weekly, and monthly evaluations. The study concludes that the program has been implemented systematically; however, improvements in several aspects are still required to enhance its overall effectiveness and achieve the intended learning objectives.